A continuous function f ( x ) is defined as follows for some non-zero constants a , b , and c : f ( x ) = ⎩ ⎨ ⎧ x + a b f ( 2 x ) + c for ∣ x ∣ < 2 for ∣ x ∣ ≥ 2 . Find the value of a 1 0 0 + b 1 0 0 + c 1 0 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
At the last fourth line, why 2 ( 2 x ) + c = x + 2 a + c ? I know that a + c = 0 , but that isn't used.
Log in to reply
Whoops, typo, sorry.
Log in to reply
Ok, I know what you write just now. Thanks!
Are you using some sort of rational zeros theorem to rule out other cases? Why do you only check + / − 2
Log in to reply
Since f is continuous everywhere, in particular f is continuous on x = 2 , − 2 .
Any possible discontinuity would be due to discontinuity at x = ± 2 . Therefore we require a ± 2 = b ( a ± 1 ) + c . Subtracting and adding the two equations gives { 4 = 2 b 2 a = 4 a + 2 c so that b = 2 and c = − a . Therefore a 1 0 0 + b 1 0 0 + c 1 0 0 = a 1 0 0 + 5 0 − a 1 0 0 = 5 0 .
Notice, both parts of the piecewise function are linear, therefore, they are themselves, continuous over their given domain. So for the piecewise function as a whole to be continuous, the 2 parts should cross at a common point, in other words, x + a = b f ( 2 x ) + c at x = ± 2 or 2 + a = b ( 1 + a ) + c (1) and a − 2 = b ( a − 1 ) + c (2) 4 = 2 b ⟹ b = 2 Subtract equation 2 from 1 a + 2 = 2 + 2 a + c a = 2 a + c ⟹ a = − c Putting this into the given expression, we get − c 1 0 0 + 2 1 0 0 + c 1 0 0 = 5 0 + c 1 0 0 − c 1 0 0 = 5 0
f ( x ) = 2 b x + a b + c
f ( 2 ) = b + a b + c = 2 + a , f ( − 2 ) = − b + a b + c = − 2 + a
Subtract two equations: 2 b = 4 , b = 2 , a = − c
Thus, since a 1 0 0 + c 1 0 0 = 0 , the answer is b 1 0 0 = 5 0 .
We need to ensure that the graph is continuous at x = − 2 and x = 2 , which will occur when both pieces of the function are equal at the corresponding x-values.
x = − 2 ⟹ f ( x ) = − 2 + a = b f ( − 1 ) + c ⟹ − 2 + a = b ( − 1 + a ) + c ⟹ − 2 + a = − b + a b + c
x = 2 ⟹ f ( x ) = 2 + a = b f ( 1 ) + c ⟹ 2 + a = b ( 1 + a ) + c ⟹ 2 + a = b + a b + c
Subtracting the second equation from the first leaves us with − 4 = − 2 b ⟹ b = 2 .
When we plug 2 in for either equation, we will end up with a + c = 0 , or c = − a . This implies that a 1 0 0 + c 1 0 0 = 0 .
Therefore, our answer is 2 1 0 0 = 5 0 .
The whole function is:
f ( x ) = ⎩ ⎨ ⎧ x + a 2 f ( 2 x ) − a for ∣ x ∣ < 2 for ∣ x ∣ ≥ 2
Now we must prove that this function is continuous. For some ∣ x ∣ ≥ 2 , the second expression will apply, and f ( 2 x ) will be computed. This will happen again and again until we reach f ( 2 n − 1 x ) = 2 f ( 2 n x ) − a and ∣ 2 n x ∣ < 2 . This will have an output of 2 ( 2 n x + a ) − a = 2 n − 1 x + a . This will substitute f ( 2 n − 1 x ) in the previous expression, and we will be left with 2 n − 2 x + a . The process continues recursively until we are left with 2 ( 2 x + a ) − a = x + a . Because this will be true for all real x-values, f ( x ) will be a continuous line.
Problem Loading...
Note Loading...
Set Loading...
Look no more, as we're only going to observe when x = ± 2 .
For x = 2 ,
x → 2 − lim f ( x ) = f ( 2 ) 2 + a = b f ( 1 ) + c 2 + a = b ( a + 1 ) + c
For x = − 2 ,
x → − 2 + lim f ( x ) = f ( − 2 ) − 2 + a = b f ( − 1 ) + c − 2 + a = b ( a − 1 ) + c
Subtracting the latter from the former, we see that b = 2 and a + c = 0 . ⇒ a 1 0 0 + c 1 0 0 = 0
Therefore the answer is 5 0 .
Now to prove it's continuous.
for 2 ≤ ∣ x ∣ < 4 , we notice that f ( x ) = 2 f ( 2 x ) + c = x + 2 a + c = x + a .
Oh. This is the same as when 1 ≤ ∣ x ∣ < 2 .
We can immediately notice that this pattern will keep holding for all reals x .
Therefore the entire function is equal to f ( x ) = x + a , proving f ( x ) is continuous. □